2013
DOI: 10.1371/journal.pone.0072911
|View full text |Cite
|
Sign up to set email alerts
|

Presence in the Pre-Surgical Fine-Needle Aspiration of Potential Thyroid Biomarkers Previously Identified in the Post-Surgical One

Abstract: Fine-needle aspiration biopsy (FNA) is usually applied to distinguish benign from malignant thyroid nodules. However, cytological analysis cannot always allow a proper diagnosis. We believe that the improvement of the diagnostic capability of pre-surgical FNA could avoid unnecessary thyroidectomy. In a previous study, we performed a proteome analysis to examine FNA collected after thyroidectomy. With the present study, we examined the applicability of these results on pre-surgical FNA. We collected pre-surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In the present study, we investigate the potential application of MALDI‐IMS in thyroid cytopathology for other lesions that are difficult to diagnose. Moreover, we suggest, based on these results, that larger trials should be included in proteomic thyroid pathology research in order to promote investigations that could potentially enable the discovery of more feasible and cost‐effective diagnostic tools (immunohistochemistry) …”
Section: Introductionmentioning
confidence: 97%
“…In the present study, we investigate the potential application of MALDI‐IMS in thyroid cytopathology for other lesions that are difficult to diagnose. Moreover, we suggest, based on these results, that larger trials should be included in proteomic thyroid pathology research in order to promote investigations that could potentially enable the discovery of more feasible and cost‐effective diagnostic tools (immunohistochemistry) …”
Section: Introductionmentioning
confidence: 97%
“…[13] A few studies have described the identification of biomarkers to improve the differential diagnosis of TCPTC from cPTC lesions. [39,40] For example, Nardone et al have revealed that TCPTC specimens expressed significantly greater levels of c-Met than other forms of PTC and benign thyroid disease. [40] In this study, we revealed for the first time that several biomarkers showed excellent predictive values not only for the differential diagnosis of TCPTC from normal tissues but also for the differential diagnosis of TCPTC from cPTC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For 1D western blot (WB), all samples were processed to validate different protein expressions found with 2D analysis. Aliquots (25 μg of proteins) of each sample (23 E-PM, 10 B-PM, 14 benign, and 14 lung carcinoma) were solubilized with a SDS sample buffer (Laemmli solution), and proteins were separated by 12% SDS-PAGE under reducing conditions and WB was carried out as previously described [14] . Before blocking the nitrocellulose, membranes were reversibly stained with 1 mM RuBP as previously described [10] .…”
Section: Methodsmentioning
confidence: 99%